2014
DOI: 10.1097/igc.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Radical Vaginal Trachelectomy After Laparoscopic Staging and Neoadjuvant Chemotherapy in Women With Early-Stage Cervical Cancer Over 2 cm: Oncologic, Fertility, and Neonatal Outcome in a Series of 20 Patients

Abstract: Laparoscopic lymphadenectomy followed by NACT and RVT in pN0 patients with cervical cancer of more than 2 cm seems to be an oncologically safe procedure with promising fertility outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 29 publications
0
79
0
Order By: Relevance
“…The impact of neoadjuvant chemotherapy on stenosis is unclear. Based on the limited articles published in the literature, the incidence of cervical stenosis after neoadjuvant chemotherapy and VRT, which varied from 16.7% to 25%, was higher than that without neoadjuvant chemotherapy [29][30][31]. Robova et al hold the opinion that this might due to change of the tissues after chemotherapy.…”
Section: Discussionmentioning
confidence: 94%
“…The impact of neoadjuvant chemotherapy on stenosis is unclear. Based on the limited articles published in the literature, the incidence of cervical stenosis after neoadjuvant chemotherapy and VRT, which varied from 16.7% to 25%, was higher than that without neoadjuvant chemotherapy [29][30][31]. Robova et al hold the opinion that this might due to change of the tissues after chemotherapy.…”
Section: Discussionmentioning
confidence: 94%
“…A variety of chemotherapeutic protocols have been used followed by fertility-sparing surgery. The first-line combination of TIP (paclitaxel, Ifosfamide and cisplatin) or TEP (paclitaxel, epirubicin and cisplatin) is currently most often used [7,11,12,14,15]. There are more complete responses, but the interval between chemotherapy normally varies between 21 and 28 days.…”
Section: Discussionmentioning
confidence: 98%
“…Lymphadenectomy before NAC is probably a safer procedure, mainly because fertility-sparing surgery is offered only to "true" lymph node negative patients [12]. NAC reduced the number of lymph node positive patients [5,13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NACT also allows for a possible decrease in the extent of surgery to preserve some cervical tissue to achieve an improved pregnancy outcome. Marchiole et al (15), Tsuji et al (16) and Lanowska et al (17) reported that 28 patients whose tumours were >2 cm or who had chemosensitive bulky disease received NACT, followed by fertility-sparing surgery, which consisted of RT and lymphadenectomy. Of these cases, one developed recurrent disease.…”
Section: Discussionmentioning
confidence: 99%